Study of analgesic property of diacerein in rat - Upadhyay, Rajlaxmi; Siddhartha, Goutam; Upadhyay, Manas Ranjan; Swain, Trupti Rekha (International Journal of Research in Medical Sciences, 2020)
Background: Diacerein has been known as an anti-osteoarthritic agent that is usually given along with other analgesic drugs. Still there is no evidence of the analgesic effect of diacerein alone. So this pilot study was undertaken to assess the analgesic property at supra-spinal level by using the tail-flick method. Methods: Diacerein at doses of 50, 100 and 200 mg/kg was given to Albino wistar rats weighing approximately 100-200 grams along with distilled water as placebo. All drugs were given by oral routes and the analgesic effect was evaluated using analgesiometer at baseline, 15 min, 30 min, 60 min and 120 min. Analgesic activity was measured as change in tail flick latency from baseline in animals. Results: Diacerein showed significant increase in tail flick latency and showed promising analgesic activity compared to placebo starting from 15 mins till 60 mins. However the effect persisted up to one hour only and after which it started decreasing. Conclusions: Diacerein at all the three doses possess dose dependant analgesic activity that is maximally effective up to 60 minutes.